Early Stages of Alzheimer's Disease: Evolving the Care Team for Optimal Patient Management - Galvin, James E.; Aisen, Paul; Langbaum, Jessica B.; Rodriguez, Eric; Sabbagh, Marwan; Stefanacci, Richard; Stern, Robert A.; Vassey, Elizabeth A.; de Wilde, Arno; West, Neva; Rubino, Ivana (Frontiers in Neurology, 2021)
Alzheimer’s disease (AD) is a progressive, neurodegenerative disease that creates complex challenges and a significant burden for patients and caregivers. Although underlying pathological changes due to AD may be detected in research studies decades prior to symptom onset, many patients in the early stages of AD remain undiagnosed in clinical practice. Increasing evidence points to the importance of an early and accurate AD diagnosis to optimize outcomes for patients and their families, yet many barriers remain along the diagnostic journey. Through a series of international working group meetings, a diverse group of experts contributed their perspectives to create a blueprint for a patient-centered diagnostic journey for individuals in the early stages of AD and an evolving, transdisciplinary care team. Here, we discuss key learnings, implications, and recommendations.